Evaluating oral swab samples for PRRSV surveillance in weaning-age pigs under field conditions - Osemeke, Onyekachukwu Henry; VanKley, Nathan; LeFevre, Claire; Peterson, Christina; Linhares, Daniel C. L. (Frontiers in Veterinary Science, 2023)
The use of serum and family oral fluids for porcine reproductive and respiratory syndrome virus (PRRSV) surveillance in weaning-age pigs has been previously characterized; both sampling options have advantages, as well as some limitations, prompting a need to evaluate other sample types for use in PRRSV surveillance for this age group of pigs; thereby expanding sample options for veterinarians and producers. Oral swab sampling is a simple, noninvasive sampling technique easily done under field conditions and is routinely used for swine pathogen investigations; however, there is limited information on the detection rates of PRRSV RNA in oral swabs compared to other commonly used specimens under field conditions. Therefore, the objective of this study was to compare the PRRSV reverse-transcription real-time polymerase chain reaction (RT-rtPCR) test outcomes of matched oral swabs (OS) and sera samples obtained from weaning-age pig litters. Six hundred twenty-three weaning-age piglets from 51 litters were each sampled for serum and OS. PRRSV RT-rtPCR positivity rate was higher in serum samples (24 of 51 litters, 83 of 623 pigs, with a mean Ct of RT-rtPCR-positive samples per litter ranging from 18.9 to 32.0) compared to OS samples (15 of 51 litters, 33 of 623 pigs, with a mean Ct of RT-rtPCR positive samples per litter ranging from 28.2 to 36.9); this highlights the importance of interpreting negative RT-rtPCR results from OS samples with caution. Every litter with a positive PRRSV RT-rtPCR OS had at least one viremic piglet, highlighting the veracity of positive PRRSV RT-rtPCR tests using OS, in other words, there was no evidence of environmental PRRSV RNA being detected in OS. Cohen’s kappa analysis (C_k = 0.638) indicated a substantial agreement between both sample types for identifying the true PRRSV status of weaning-aged pigs.